ENVIRONMENTAL PROBLEMS CAUSED BY MAN-MADE EFFECTS AND MEASURES TO ELIMINATE THEM (Journal of Universal Science Research, 2025)
Man has appeared on earth and has always been in close contact with nature. Every person lives on the earth, works, conducts economic activities, and uses the material resources of nature from the moment he comes into the world and begins to breathe. During this time, it has its influence on nature. As a result of human work, various wastes are released into the environment. Part of the waste affects the atmosphere, the other affects the water, earth, flora and fauna, and accumulates over time. It is now fully confirmed that their gradual accumulation over the years causes various problems, sometimes very dangerous problems for human life. The main content of the article is to review and study environmental problems caused by man- made effects, proper use of nature in the course of human activity, and measures to eliminate environmental problems.